The Major Challenges and Opportunities of E-Learning for Teachers and Students in Covid-19 Panadamic: A Descriptive Study - Bareq Raad Raheem Bareq Raad Raheem; Zanyar Nathir Ghafar (Journal Of Social Science (JoSS), 2023)
Background: The worldwide spread of the Coronavirus has presented several challenges to the educational sector in recent years. It is crucial to understand the students' experiences with online learning amid the Covid-19 pandemic in view of the present study. Even though this issue has been studied extensively, more is still needed to learn about the challenges students face and the precise strategies they use to overcome them. The consequences of online learning during the Covid-19 outbreak undoubtedly offered many opportunities while offering specific challenges that influenced the overall psychological health of teachers and students. Aim: This study will thoroughly analyse the opportunities, issues, and psychological repercussions of students' and teachers' rapid move to online learning during the COVID-19 pandemic. Method: A descriptive qualitative method using the literature review has been adopted in the present study. The present study's data is obtained from the previous related published works to draw out the objectives of the present study. Findings: The research revealed that the pandemic caused by Covid-19 had the most effects on the students' psychological health and the overall quality of their educational experiences. The techniques that students employ the most often include resource management and utilisation, seeking assistance, improving technical aptitude, learning time running techniques, and effectively maintaining control over the learning environment. The researchers focus on the implications of these findings for ongoing research, classroom instruction, and politicians' decisions. The atmosphere in which they learned at home was the most challenging assignment for learning technological literacy and competency.